Reunion eaudiobook - Cabot, Meg (The Mediator, 2005)
The Mediator series has earned #1 New York Times best-selling author Meg Cabot unrivaled praise for her portrayal of a smart, courageous heroine. Suze Simon, a mediator who guides ghosts to the afterlife, is having a great time with her best friend from New York. But then four ghosts, the "RLS Angels," show up looking for revenge. The angry spirits died in a car accident and they blame Michael Meducci, a nerdy boy who has a crush on Suze.